Population and Culture Age Influence the Microbiome Profiles of House Dust Mites - Hubert, Jan; Nesvorná, Marta; Kopecký, Jan; Erban, Tomáš; Klimov, Pavel (Microbial ecology, 2019)
Interactions with microorganisms might enable house dust mites (HDMs) to derive nutrients from difficult-to-digest structural proteins and to flourish in human houses. We tested this hypothesis by investigating the effects of changes in the mite culture growth and population of two HDM species on HDM microbiome composition and fitness. Growing cultures of laboratory and industrial allergen-producing populations of Dermatophagoides farinae (DFL and DFT, respectively) and Dermatophagoides pteronyssinus (DPL and DPT, respectively) were sampled at four time points. The symbiotic microorganisms of the mites were characterized by DNA barcode sequencing and quantified by qPCR using universal/specific primers. The population growth of mites and nutrient contents of mite bodies were measured and correlated with the changes in bacteria in the HDM microbiome. The results showed that both the population and culture age significantly influenced the microbiome profiles. Cardinium formed 93% and 32% of the total sequences of the DFL and DFT bacterial microbiomes, respectively, but this bacterial species was less abundant in the DPL and DPT microbiomes. Staphylococcus abundance was positively correlated with increased glycogen contents in the bodies of mites, and increased abundances of Aspergillus, Candida, and Kocuria were correlated with increased lipid contents in the bodies of mites. The xerophilic fungus Wallemia accounted for 39% of the fungal sequences in the DPL microbiome, but its abundance was low in the DPT, DFL, and DFT microbiomes. With respect to the mite culture age, we made three important observations: the mite population growth from young cultures was 5-8-fold higher than that from old cultures; specimens from old cultures had greater abundances of fungi and bacteria in their bodies; and yeasts predominated in the gut contents of specimens from young cultures, whereas filamentous mycelium prevailed in specimens from old cultures. Our results are consistent with the hypothesis that mites derive nutrients through associations with microorganisms.
Keywords: druhová specificita; populační dynamika; Pyroglyphidae; zvířata; bakteriální RNA; houby; kvantitativní polymerázová řetězová reakce; DNA Barcoding, Taxonomic; mikrobiota; RNA, Bacterial; Real-Time Polymerase Chain Reaction; Population Dynamics; Animals; Species Specificity; RNA ribozomální 18S; RNA, Ribosomal, 18S; RNA, Ribosomal, 16S; Microbiota; RNA, Fungal; fungální RNA; Fungi; taxonomické DNA čárové kódování; Bacteria; RNA ribozomální 16S